Identifying viral parameters from in vitro cell cultures - Iwami, Shingo; Sato, Kei; De Boer, Rob J.; Aihara, Kazuyuki; Miura, Tomoyuki; Koyanagi, Yoshio (Frontiers in Microbiology, 2012)
Current in vitro studies of viral replication deliver detailed time courses of several virological variables, like the amount of virions and the number of target cells, measured over several days of the experiment. Each of these time points provides a snap-shot of the virus infection kinetics and is brought about by the complex interplay of target cell infection, and viral production and death. It remains a challenge to interpret this data quantitatively and reveal the kinetics of these underlying processes to understand how the viral infection depends on these kinetic properties. In order to decompose the kinetics of virus infection, we introduce a method to “quantitatively” describe the virus infection in in vitro cell cultures, and discuss the potential of the combinational analyses for experimental and computational virology.